Boundaryless Career: Research Perspectives - Bednarska-Wnuk, Izabela (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The purpose of the article is to identify and describe the main constructs of a boundaryless career – psychological mobility, a boundaryless mindset, and organisational mobility. In its empirical layer, the aim is to determine the relationship between these constructs and to determine whether they depend on such independent variables as gender and age. Research Design & Methods: The article presents the results of quantitative research, which was conducted among 259 employees by means of a questionnaire. Findings: The respondents are characterised by a well-developed boundaryless mindset and a low level of organisational mobility. Women and men exhibited equal levels for both constructs, while for particular age categories the levels vary. The vast majority of respondents do not wish to pursue careers in only one organisation. Implications / Recommendations: Contemporary employees are characterised by openness and readiness to change, are eager to learn new things, have high expectations regarding their own employability, and are looking for development paths outside their current workplace. Contribution: The research provides important guidance for organisations in the context of employees’ behaviour in the labour market.